Malignant hypercalcemia as the debut of acute lymphoblastic leukemia in a pediatric patient—a diagnostic and therapeutic approach: Case report - Bonilla Gonzalez, Carolina; Vargas Muñoz, Sarha M.; Contreras Diaz, María Luisa; Obando Belalcazar, Evelyn; Uribe, Camila (Frontiers in Pediatrics, 2022)
Background: Hypercalcemia is a rare metabolic disorder in the pediatric population, with several differential diagnosis that resemble hematologic malignancies. In cases of severe hypercalcemia, therapeutic strategies other than hyperhydration, such as the use of bisphosphonates, have been described. Case presentation: We present the case of a previously healthy 12-year-old male who was admitted to the emergency department due to fatigue, hyporesponsiveness, and progressively worsening poor appetite for the prior 19 days. Initial laboratory tests revealed severe hypercalcemia (total calcium: 19 mg/dl), hyperphosphatemia, elevated creatinine, and hyperuricemia. Management with hyperhydration and xanthine oxidase inhibitor (allopurinol) was provided. The patient was transferred to the pediatric intensive care unit where treatment with furosemide, systemic corticosteroid, and zoledronic acid was started. Metabolic, infectious, renal, and endocrinological causes were excluded. Follow-up paraclinical studies showed a progressive hematologic involvement with heterogeneous hypochromic microcytic anemia, thrombocytopenia and, elevated lactic dehydrogenase. Bone marrow aspiration and biopsy were performed, which confirmed the diagnosis of B-precursor acute lymphoblastic leukemia. Hypercalcemia was resolved 72 hours after the application of bisphosphonates. Conclusion: Hypercalcemia as an oncological metabolic emergency in the onset of acute lymphoblastic leukemia is uncommon in children. The use of IV bisphosphonates is an effective therapy in the early resolution of the condition. We present the case of a 12-year-old patient with hypercalcemia of malignancy who responded favorably to the use of bisphosphonates single dose.